A Theoretical and Empirical Approach to the Value of Information in Risky Markets - Antonovitz, Frances; Roe, Terry (The Review of Economics and Statistics, 1986)
The theory of the competitive firm under price uncertainty is used to develop a money metric of a producer's willingness to pay for additional information. This concept is extended to the market by formulating ex-ante and ex-post measures of the value of a rational expectations forecast. The empirical feasibility of these measures are demonstrated by application to a simple two equation model of an agricultural market.